Kingdom hearts II. 1 - Amano, Shiro; Nomura, Tetsua (Yen Press, 2013)
A boy named Roxas concludes his summer vacation with his three best friends in Twilight Town. But strange things begin happening around Roxas and he has dreams of a boy named Sora. Soon Roxas is drawn into a dangerous adventure with Donald, Goofy, and other Disney characters.